Conservative thought and the equal rights amendment in Kansas - Lowenthal, Kristi (Kansas State University, 2008)
Despite an impressive history of woman-friendly legislation, Kansans tend to be socially conservative. The Equal Rights Amendment, first proposed in 1923, was the culmination of over a century's worth of women's activism attempting to remove the strictures of coverture and to recognize women as citizens in their own right, not as wives or as mothers of male citizens. After largely ignoring the amendment for fifty years, Congress finally passed the ERA in 1972 and submitted it to the states for ratification. Almost immediately, the real and imagined consequences of the legislation provoked a passionate debate among mostly middle-class white women about the meaning of American womanhood. Liberals hoped that the ERA would remove existing barriers to women's educational and professional life; conservatives feared that the ERA would cause women to focus on selfish interests outside of their households, rotting the foundations of family life and American strength. In Kansas, women from both camps converged to discuss the future of the ERA at the feminist-organized Kansas Women's Weekend of July 15-17, 1977, resulting in Kansas sending a conservative faction to the federally funded National Women's Conference later that year. Conservatives failed to derail the convention's feminist agenda, nor were they able to enact a rescission of Kansas' ratification, but in the long run they succeeded in creating widespread uneasiness about the social consequences of the ERA. The vitriolic anti-ERA campaign demonstrated the extent to which female dependency still defined both male and female conservatives' views on the interrelatedness of family, religion, manliness, and national strength. This dissertation explores a volume of letters to Kansas legislators expressing anti-ERA sentiment. The letters provide a unique lens through which to examine the passions aroused by the ERA among grassroots conservatives. Contextualizing this issue are other conservative reactions to feminist activity from the Revolution onward that consistently demonstrate how conservatives valorize female dependency. Although the liberal position regarding women's rights has changed significantly over two hundred years, conservative reaction has invariably embraced and elevated the patriarchal family as proper and necessary to the smooth functioning of a Christian republic.
Keywords: Conservatism; Kansas; Women; Equal Rights Amendment; ERA; History, Modern (0582); History, United States (0337); Women's Studies (0453)